The Effect of The Use of Financial Technology and Social Media on Financial Performance of UMKM Kuliner in Kecamatan Seberang Ulu 2 Palembang - Siti Awalani Cahyani; Alwi Alwi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of Financial Technology (Fintech) and Social Media on the Financial Performance of Culinary MSMEs in Seberang Ulu II District, Palembang City. The rapid development of digital technology encourages small business actors to adapt in order to remain competitive, especially through digital payment systems and online promotion platforms. The objective of this study is to determine whether the use of fintech and social media has a significant effect, both partially and simultaneously, on the financial performance of culinary MSMEs.This research uses a quantitative approach with a survey method. The population consists of culinary MSMEs in Seberang Ulu 2, with a total sample of 91 respondents, selected using the Slovin formula. The data collection technique is through questionnaires, and the data analysis technique used is multiple linear regression, supported by the Pearson correlation test and the coefficient of determination (R²). The results of the study show that both fintech and social media have a positive and significant effect on the financial performance of MSMEs, both partially and simultaneously. The coefficient of determination indicates that 22.9% of the variation in financial performance can be explained by the two independent variables.It can be concluded that digital transformation through fintech and social media is an effective strategy to improve the financial performance of culinary MSMEs in the digital era.